2021
DOI: 10.3389/fsurg.2021.758947
|View full text |Cite
|
Sign up to set email alerts
|

Hydropic Ear Disease: Correlation Between Audiovestibular Symptoms, Endolymphatic Hydrops and Blood-Labyrinth Barrier Impairment

Abstract: Research Objective: To investigate the correlation between clinical features and MRI-confirmed endolymphatic hydrops (EH) and blood-labyrinth barrier (BLB) impairment.Study Design: Retrospective cross-sectional study.Setting: Vertigo referral center (Haga Teaching Hospital, The Hague, the Netherlands).Methods: We retrospectively analyzed all patients that underwent 4 h-delayed Gd-enhanced 3D FLAIR MRI at our institution from February 2017 to March 2019. Perilymphatic enhancement and the degree of cochlear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
1
9
0
1
Order By: Relevance
“…We demonstrated that the MD-140 endotype is associated with bilateral clinical disease and a trend toward a male predominance, which is in accordance with previous studies ( 27 , 29 ). Generally, MD symptoms manifest in the fourth decade of life ( 31 ). The presumed congenital origin of the MD-140 subtype raises the question of whether these patients would manifest symptoms earlier in life compared with the rest of the MD population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that the MD-140 endotype is associated with bilateral clinical disease and a trend toward a male predominance, which is in accordance with previous studies ( 27 , 29 ). Generally, MD symptoms manifest in the fourth decade of life ( 31 ). The presumed congenital origin of the MD-140 subtype raises the question of whether these patients would manifest symptoms earlier in life compared with the rest of the MD population.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for evaluating EH and perilymphatic enhancement have been reported previously ( 31 ). Briefly, EH was scored as a blinded consensus reading by one head and neck radiologist (SH) and one PhD student (LP) on a 4-point scale for vestibular hydrops and a 3-point scale for cochlear hydrops, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to computed tomography images, MR images cannot be calibrated via an analog to Hounsfield units. Another factor which might explain the large standard deviation in measured evaluation is that the disruption of the BLB, which is responsible for the impaired PE, is correlated to the EH grade and duration of the disease [ 3 , 18 ]. Moreover—in our experience—there seems to be a gradient in the enhancement of the basal turn of the cochlea with a more pronounced enhancement in the posterolateral part of the basal turn.…”
Section: Discussionmentioning
confidence: 99%
“…Распространенность и заболеваемость БМ в целом у мужчин и женщин увеличилась за последние 5 лет [5]. Средний возраст дебюта БМ достигает максимума в 40-50 лет, у 10% пациентов с БМ начало заболевания было в возрасте ≥65 лет [13]. По другим данным, распространенность увеличивается с возрастом, причем пик заболеваемости приходится на возрастную группу 61-70 лет [3,14].…”
Section: эпидемиологияunclassified